Relationship between knowledge and mother’s attitude towards the growth and development of children aged 0 12 month in Nagori Sahkuda Bayu Gunung Malela District Simalungun Regency - Sukaisi (Poltekkes Kemenkes Medan, 2021)
Child health care efforts are aimed at preparing future generations to be healthy, intelligent, and of high quality and to reduce child mortality. The achievement of optimal child growth and development depends on the biological potential. The purpose of this study was to determine the relationship between mother's knowledge and attitudes towards the growth and development of children aged 0-12 months in Nagori Sahkuda Bayu, Gunung Malela District, Simalungun Regency. This study is an analytic survey, conducted on 77 mothers. In this study to measure the knowledge, attitudes of mothers about growth and development of children aged 0-12 months and measure the growth and development of children. Knowledge and attitude data was collected using a questionnaire, and measuring children's growth and development was using the Developmental Pre-Screening Questionnaire (KPSP). The data is processed by Chi-Square. The respondents in this study were generally 20-30 years old, with low education and average housewives. The results obtained from the mother's knowledge about child growth and development with sufficient knowledge (40.2%), the mother's attitude generally agreed (62.3%) for growth and development, and the measurement of child growth and development with KPSP was good. There is a significant relationship between knowledge and attitudes of mothers with child growth and development. The role of health workers in assisting mothers to monitor knowledge and child development.